1987
DOI: 10.1080/00268978700101171
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation theory for the thermodynamic properties of liquid nitrogen using model potentials

Abstract: A statistical mechanical perturbation theory due to Fischer has been used to calculate thermodynamic properties of liquid nitrogen for model intermolecular potentials due to Cheung and Powles (CP), Raich and Gillis (RG), and Berns and van der Avoird (BV). Refinements in the numerical implementation of the Fischer theory are described. Results for the CP potential agree well with both simulation and experimental data except at high density and high temperature. Differences between theory and experiment are usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Therefore, the method can now he used to derive a number of thermodynamic properties. The calculated values for the configurational free energy for a moderately soft potential are in excellent agreement with those of Watanabe et al [20] and Fischer [3] as shown in table 1. Also, the calculated values for the excess specific heat at the constant volume are almost identical with those given by Fischer et al [6] (see Table 2.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, the method can now he used to derive a number of thermodynamic properties. The calculated values for the configurational free energy for a moderately soft potential are in excellent agreement with those of Watanabe et al [20] and Fischer [3] as shown in table 1. Also, the calculated values for the excess specific heat at the constant volume are almost identical with those given by Fischer et al [6] (see Table 2.…”
Section: Resultssupporting
confidence: 82%
“…Results of the perturbation theory for diatomic molecules for L = 0.3292 (corresponding to a moderately soft potential) at T* = kT/e = 2.0 where e is the depth of the potential well of Lennard-Jones type. Perturbation theory values for the reduced configurational free energy Ar at densities (/90 "3) obtained in the present study are compared with those of Watanabe et al[20] and Fischer[3].…”
mentioning
confidence: 68%
“…For diatomic molecules, the nonspherical perturbation approach initiated by Fischer [11 is the most successful of the perturbation theories, and has already achieved much success in predicting the thermodynamic properties for liquids and liquid mixtures [2-51. In view of the importance of the diatomic molecules with two centre Lennard-Jones potential (2CLJ), several refinements [2,3] have already been proposed for the numerical calculation following Fischer's theory. In order to increase the precision further, we have now introduced another important refinement which will be reported in this note.…”
mentioning
confidence: 99%